Does Financial Risk Matter for Financial Performance in Sharia Banks? - Amijaya, Rachmania Nurul Fitri; Alaika, Rochmatulloh (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This study seeks to examine the impact of operational, liquidity, and credit risks on financial performance (ROA) at national Islamic commercial banks from 2015 to 2021. The model includes control variables such as technological risk (E-Banking) and macroeconomic variables (BI rate and inflation). This study used seven national Islamic banking businesses as examples. This work employs the panel data regression technique to investigate a mixture of time series from 2015 to 2021. In this study, the independent variables are credit risk as measured by Non-Performing Finance (NPF), liquidity risk as measured by Finance to Deposit Ratio (FDR), operational risk as measured by Operations Expenses to Operations Income (BOPO), and performance bank finances as measured by Return on Assets (ROA). According to the study's findings, the variable credit risk (NPF), operational risk (BOPO), and technological risk (E-Banking) all significantly and negatively affect financial performance (ROA). Meanwhile, neither liquidity risk nor inflation has a significant positive impact on financial performance (ROA). Furthermore, the BI rate has a negative, but not statistically significant, impact on financial performance (ROA).